Complete left sided Duplex system with Upper Moiety Hydroureteronephrosis with Ectopic insertion of upper moiety Ureter Beyond the Sphincter( a rare Phenomenon with unusual presentation): Case Report and Review - Bihari Sharma, Shyam; Tariq, Tariq; Gupta, Shubham; Mahajan, Atharv; Bhardwaj, Shruti; Prasher, Meher (Journal of Neonatal Surgery, 2025)
Background: Complete duplex systems are rare congenital anomalies of the urinary tract and usually present later in childhood with continuous dribbling or recurrent urinary tract infections (UTIs). Presentation in early infancy is unusual and may be easily overlooked. Case Presentation: We describe the case of a 3-month-old female infant who presented with high-grade fever, recurrent UTIs, and persistent dribbling of urine despite apparently normal voiding. The mother also observed that the child cried and strained forcefully during micturition, which heightened concern. Imaging revealed a complete duplication of the left renal collecting system with ectopic insertion of the upper-moiety ureter into the urethra, complicated by vesicoureteral reflux (VUR) and moderate hydroureteronephrosis. Laboratory evaluation confirmed sepsis, and preoperative workup revealed deranged coagulation (prolonged PT/INR) secondary to urosepsis which was corrected with culture documented IV antibiotics and coagulopathy got corrected once sepsis part was over. The child underwent modified Politano-Leadbetter ureteric reimplantation after cystoscopy... Conclusion: Ectopic ureters with insertion beyond the sphincter may present early with continuous dribbling and infections. Early recognition and timely surgical correction are essential to preserve renal function and prevent long-term morbidity.